2021
DOI: 10.1071/fp20386
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic programming of Rhododendron chrysanthum leaves following exposure to UVB irradiation

Abstract: Excessive UVB reaching the earth is a cause for concern. To decipher the mechanism concerning UVB resistance of plants, we studied the effects of UVB radiation on photosynthesis and metabolic profiling of Rhododendron chrysanthum Pall. by applying 2.3Wm−2 of UVB radiation for 2days. Results showed that maximum quantum yield of PSII (Fv/Fm) and effective quantum yield of PSII (φPSII) decreased by 7.95% and 8.36%, respectively, following UVB exposure. Twenty five known metabolites were identified as most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The artificial radiation UV-B (Philips, Ultraviolet-B TL 20W/01 RS, Amsterdam, NY, The Netherlands) used in this experiment was the same as previously described [ 7 , 37 , 38 ]. In short, the leaves of R. chrysanthum were exposed to UVB artificial radiation for six replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The artificial radiation UV-B (Philips, Ultraviolet-B TL 20W/01 RS, Amsterdam, NY, The Netherlands) used in this experiment was the same as previously described [ 7 , 37 , 38 ]. In short, the leaves of R. chrysanthum were exposed to UVB artificial radiation for six replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The chlorophyll fluorescence was obtained in order to analyze PSII quantum efficiency of plants by using an IMAGING PAM M-series (Walz, Effeltrich, Germany), and dark period of the samples was dark for 30 min before measurements. The maximum quantum yield of PSII (Fv/Fm), the effective quantum yield of PSII (φPSII), non-photochemical quenching coefficient (NPQ), and electron transport rate (ETR, μmol e –1 s –1 m –2 ) were calculated according to Zhou et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…Plant species can maintain metabolism and homeostasis via the modulation of fluidity and stability of plasma membrane under unfavorable situations [ 31 ], and saturated/unsaturated fatty acids play a particularly crucial role in membrane rigidity [ 32 ]. In this study, the levels of fatty acids increased in purple kohlrabi sprouts upon exposure to UVB radiation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that the increase in the levels of fatty acids may help sustain the metabolism and homeostasis in purple kohlrabi sprouts exposed to UVB radiation. Similarly, Zhou et al [ 32 ] have suggested that UVB radiation induces an increase in the levels of fatty acids, organic acids, and flavonoids in the leaves of Rhododendron chrysanthum irradiated by UVB radiation [ 31 ], and Moorthy and Kathiresan [ 33 ] have reported an increase in the levels of myristoleic acid in mangroves under high dose of UVB radiation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%